Gaseous fuels, a windfall for artisanal lagoon transportation in Abidjan, Ivory Coast - Soro , Nemeloh; Estelle Gisèle Kabran, Gnankon; Zoma, Vincent (International Journal of Scientific Research and Management (IJSRM), 2022)
In Abidjan, the daily movements of people are made from different means of transport. Among these different means of transport is artisanal lagoon transport. This one shares the lagoon water body with other modern transport companies. For the operation of their activity, small-scale lagoon carriers use diesel, a fuel that continues to cause problems for small-scale lagoon carriers, so much so that it is important to think about palliative solutions such as the use of gaseous fuels. Thus, this study proposes to analyze the contributions of the use of gaseous fuels (LPG) in artisanal lagoon transport on the lagoon water body of Abidjan. To do this, the survey focused on the artisanal lagoon carriers, the lagoon environment monitoring structures that are the DOMSE and the CIAPOL. Research shows that the use of gaseous fuels in the field of artisanal lagoon transport would allow artisanal carriers to make economic gains. It would be an asset in the face of competition from other modern and semi-modern societies by playing on prices and distances, and would be a more ecological source of energy than other commonly used fuels.